2018
DOI: 10.1021/acs.jafc.8b01849
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Tyrosinase-Inhibitory and Copper-Chelating Peptides from Hydrolyzed Rice-Bran-Derived Albumin

Abstract: Rice-bran albumin (RBAlb), which shows higher tyrosinase-inhibitory activity than other protein fractions, was hydrolyzed with papain to improve the bioactivity. The obtained RBAlb hydrolysate (RBAlbH) was separated into 11 peptide fractions by RP-HPLC. Tyrosinase inhibition and copper chelation activities decreased with increasing retention times of the peptide fractions. RBAlbH fraction 1, which exhibited the greatest activity, contained 13 peptides whose sequences were determined by using LC-MS/MS. Most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Amino acids are protein substrates and are highly safe for humans, being commonly used in cosmetic ingredients [52,53]. Studies have shown that amino acids and their derivatives are an effective measure to suppress the signs of aging, oxidative stress, and melanogenesis [52,[54][55][56][57].…”
Section: Analysis Of Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids are protein substrates and are highly safe for humans, being commonly used in cosmetic ingredients [52,53]. Studies have shown that amino acids and their derivatives are an effective measure to suppress the signs of aging, oxidative stress, and melanogenesis [52,[54][55][56][57].…”
Section: Analysis Of Amino Acidsmentioning
confidence: 99%
“…Furthermore, one or more residues of glutamic acid, lysine, aspartic acid, valine, alanine, proline, methionine, tryptophan, and phenylalanine improve the antioxidant activity [55,60]. Valine, leucine, serine, alanine, glycine, and glutamic acid have been reported to contribute to metal-chelating activity and tyrosinase-inhibition [57,61]. In T65 crude product, various residues of free and composite amino acids were detected that were capable for antioxidant, anti-aging, and anti-tyrosinase activities.…”
Section: Analysis Of Amino Acidsmentioning
confidence: 99%
“…Since the discovery of a potential protein or peptide with tyrosinase inhibitory activity from lemon skin extract in 2006 [4], reports on peptide-based skin lightening agents has increased by leaps and bounds. The anti-pigmentation mechanisms of peptides include tyrosinase inhibition [5], copper chelation [6] and melanogenesis pathway regulation [7]. Peptide was also incorporated as an active ingredient in commercial skin lightening products such as β-White TM (contains oligopeptide-68) and Melanostatine TM 5 (contains nonapeptide-1) marketed by Lucas Meyer Cosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-pigmentation peptides have been discovered from various natural protein sources including rice bran [6,9] and marine microalgae [10]. Yet, there has been no relevant study on the anti-pigmentation effect of chicken egg white-derived peptides, although this readily available protein has been traditionally used as facial masks to boost skin health.…”
Section: Introductionmentioning
confidence: 99%
“…If its function is decreased or deleted, it will lead to depigmentation diseases, such as vitiligo and leukosis [4,5], while autosomal recessive diseases in animals and humans such as Parkinson's disease are also related to tyrosinase deletion or activity decreases [6][7][8]. In addition, abnormal overexpression of its activity will lead to pigmentation diseases of the human body, such as freckles, chloasma and melanoma [9][10][11][12]. Tyrosinase is also known as a polyphenol oxidase, which is responsible for not only melanization in animals, but also browning in fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%